The Relationship Between Poverty and Economic Variables of Thailand - Kabinlapat, Pawittra; Panthamit, Nisit; Jariyapan, Prapatchon (WMS Journal of Management, 2016)
This research aimed to investigate the relationship between the incidence of poverty and economic variables of Thailand, using annually regional level data from 1995 to 2009. Econometric techniques used for analysis were Pooled OLS, Fixed Effects Model and Random Effects Model. The Fixed effects model indicated the impact of the Gini coefficient, unemployment rate and consumer price index on poverty incidence to be positive. An average monthly income per household was significant negatively correlated with poverty incidence. When dummy variables were incorporated into the analysis to determine the individual relationship region, the study found that unemployment had a positive impact on the incidence of poverty in northeastern regions, the Gini coefficient had a negative impact on the incident of poverty in northern region and the average monthly income per household had a negative impact on the incidence of poverty in Bangkok.